2008
DOI: 10.1016/j.jvs.2008.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive extracorporeal limb perfusion (HELP): A new technique for managing critical lower limb ischemia

Abstract: Blood flow through collaterals can be very significantly augmented by connection to an extracorporeal pump with isolation from the systemic circulation. The pancycle hyperperfusion can be safely repeated by implantation of an arterial access device. In the longer term, there is evidence of collateral development. When amputation is the only alternative, hypertensive extracorporeal limb perfusion should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…induced by exercise. 2 After pump disconnection, there is recovery of smooth muscle tone. At the vascular endothelial level while on the pump, there is an enormous increase in blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…induced by exercise. 2 After pump disconnection, there is recovery of smooth muscle tone. At the vascular endothelial level while on the pump, there is an enormous increase in blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of regional hyperperfusion can be used for other ischemic organs and has already been shown in the carotid circulation. 2 Furthermore, the continuous perfusion dramatically increases the total flow through a vessel without the peak perfusion pressure having to be increased, largely due to increased diastolic flow. Theoretically, this may minimize the risk of intracerebral hemorrhage while increasing collateral flow for occlusive cerebral disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that this gene therapy failed to reduce the amputation rate at 100 days significantly, but meaningful hemodynamic improvement (increase in ankle-brachial index and toe-brachial index) was found. In 2008, Lane et al 20 introduced a new technique named hypertensive extracorporeal limb perfusion for improving critical ischemia and experimented it in the lower limbs of sheep and patients. The theoretical basis of this therapy is that the high arterial pressure would result in high fluid shear stresses on the endothelial surface that will stimulate growth and remodeling of collateral vessels.…”
Section: Treatment Program Selectionmentioning
confidence: 99%